The grandest game - Barnes, Jennifer Lynn (Barnes, Jennifer Lynn. Grandest Game (Series), 2024)
Seven tickets. An island of dreams. The chance of a lifetime. Welcome to the Grandest Game, an annual competition run by billionaire Avery Grambs and the four infamous Hawthorne brothers, whose family fortune she inherited. Designed to give anyone a shot at fame and fortune, this year's game requires one of seven golden tickets to enter. With millions on the line, those seven players will do whatever it takes to win. Some of the players are in it for the money. Some for power. Some for reasons all their own. Every single one of them has secrets. Amidst it all is Grayson Hawthorne, tasked with a vital role in this year's game. But as tensions rise and the mind-bending challenges push the players to their limits--physically, mentally, and emotionally--it soon becomes clear that not everyone is playing by the rules.